Religião e religiosidade na pós-modernidade - Greuel, Sigolf (2008)
The objective of this Dissertation is to research the dimension that Pos Modernity Paradigms influence the articulation between Religion and Religiosity, and to seek ways to a pastoral action with Adolescent and Youth in this context. The first part of this work tries to understand the characteristics in the historic moment that we live. Being result of a historical evaluation, Pos-Modernity comes from Enlightenment Modernity that has placed the human being at the center, as reason and measure of every thing. In this way, it proposes a new daily routine, with a new configuration of subjects, essentially individualistic and narcissistic, intensely determined for the market economy. The emptying of the social, produced for it, results in a peculiar articulation in human relationships. The second part verifies that Religion, relegated by the Enlightenment to an absolutely secondary dimension, rises again powerfully, in a large variety of expressions. It works as any Religiosity of personal arrangement, as a result of the disillusion with Pos Modernity, where subjects seek for a transformation in their individuality and a reason to exist. For having been created from the Pos Modernity, Religion runs the risk of assuming an alienating manner in its determinants, becoming anthropocentric, fundamentalist, and a mere product of the neo-liberal market. The third part analyses the difficulty in articulating a pastoral action with Adolescents and Youths in these days, although we can see clearly that Religion is present is their imaginary. Even though that, we articulate some reflexions in order to show that it is possible to proportionate to the Adolescent and Youth a privileged place where they can have a meeting with theirselves, with another one, and with the sacred. This experience can be essential for the construction of their identity and for the seeking of their existing reason. This work also presents some principles that were considered important to an action with Adolescents and Youths: The principles of Open Door, Open Mind, Open Heart, Open Bible and Open Hand, inspired in the practice of Jesus and extracted from his meeting with an young man. We conclude with a description of some experiences in the work with Adolescents and Youths at the communities of the Center-South Catarinense Synod, context of this research.